2022
DOI: 10.2147/nss.s388863
|View full text |Cite
|
Sign up to set email alerts
|

Different Intensities of Evening Exercise on Sleep in Healthy Adults: A Systematic Review and Network Meta-Analysis

Abstract: The effects of different intensities of evening exercise on subsequent sleep remain contradictory. Thus, this systematic review and network meta-analysis aimed to compare and rank the effects of different intensities of acute evening exercise on sleep in healthy adults with good sleep. Articles were systematically searched journals indexed in the PubMed, Web of Science, Cochrane Library, Embase, and Scopus databases from inception to the 5th of May, 2022. The basic search terms included exercise, sleep and tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…The different intensities and types of exercise lead to varied effects on sleep ( 29 ). Generally, low-intensity exercises such as jogging and yoga are believed to have the most positive effects on athletes' sleep quality ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…The different intensities and types of exercise lead to varied effects on sleep ( 29 ). Generally, low-intensity exercises such as jogging and yoga are believed to have the most positive effects on athletes' sleep quality ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Exercise is recommended for improving sleep, and, in the further course, metabolism, and it has been shown that acute evening exercise before bedtime or regular exercise, respectively, do not disrupt night time sleep in adults without and with pre‐existing sleep disturbances. As one mechanistic link, the myokine brain‐derived neurotrophic factor BDNF is discussed, since it has been shown to increase sleep depth in an animal model 41–43 . However, there might be a negative effect of mistimed exercise, for instance during a time the subject is unfamiliar to.…”
Section: Chronophysiology and The Circadian Clockmentioning
confidence: 99%
“…As one mechanistic link, the myokine brain-derived neurotrophic factor BDNF is discussed, since it has been shown to increase sleep depth in an animal model. [41][42][43] However, there might be a negative effect of mistimed exercise, for instance during a time the subject is unfamiliar to.…”
Section: Chron Oph Ysi Ology and The Circadian Clockmentioning
confidence: 99%
“…In addition, exercise also improves cardiopulmonary fitness, sleep quality, and excessive daytime sleepiness [13]. A recent network meta-analysis aimed to compare the effects of different intensities of acute exercise on sleep in healthy adults with good sleep [14]. The authors reported that twenty-eight studies with 325 participants met the inclusion criteria.…”
Section: Introductionmentioning
confidence: 99%
“…The authors reported that twenty-eight studies with 325 participants met the inclusion criteria. The results revealed that there were no significant differences in terms of impact on sleep caused by different intensities of acute exercise, except when compared to no exercise [14]. For these reasons, PA is perhaps one of the most promising alternatives for improving sleep (sleep quality and number of sleep hours), because it can reduce the risk of health problems and disease through several mechanisms, including weight and inflammation reduction and increased psychological well-being [15][16][17].…”
Section: Introductionmentioning
confidence: 99%